La labor de José María de Egaña como alcalde de barrio y teniente de policía en Lima a fines del siglo XVIII - Rivasplata Varillas, Paula Ermila (2017)
Jose Maria de Egafia came from Spain to settle in Lima where he married and held the positions of mayor and lieutenant district police. Efficient and restless man who helped implement new illustrated ideas in Lima. One of his main actions was the Lima census of 1791. He was also one of the founders of the newspaper Mercurio Peruano.